2008
DOI: 10.1002/pen.21087
|View full text |Cite
|
Sign up to set email alerts
|

Nonisothermal crystallization of high density polyethylene and nanoscale calcium carbonate composites

Abstract: Nonisothermal crystallization of high density polyethylene (HDPE)/maleic anhydride-modified HDPE(manPE)/ nanoscale calcium carbonate (CaCO 3 ) nanocomposite was investigated by means of wide angle X-ray diffraction (WAXD), polarized optical microscopy (POM), and differential scanning calorimetry (DSC). WAXD indicated that the crystallinity was reduced with the addition of CaCO 3 . The spherulite size of HDPE increased in the presence of manPE, but decreased when CaCO 3 was added from observation of POM. A modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 43 publications
5
35
2
Order By: Relevance
“…Eder and Wlochowicz showed that the Ozawa method did not produce straight lines in the log[−log(1 − X t )] versus log R plot for HDPE indicating that this model was not adequate, which was also confirmed by Liu et al . Likewise, attempts to utilize the Ozawa method in the SiO 2 and CaCO 3 NA systems showed unacceptable nonlinear behavior in both the neat HDPE and composites during both primary and secondary crystallization phases . In all cases, this discrepancy was attributed to factors neglected in the Ozawa theory including secondary crystallization and dependence of lamellar thickness on the T c .…”
Section: Nonisothermal Crystallization Kineticsmentioning
confidence: 67%
See 3 more Smart Citations
“…Eder and Wlochowicz showed that the Ozawa method did not produce straight lines in the log[−log(1 − X t )] versus log R plot for HDPE indicating that this model was not adequate, which was also confirmed by Liu et al . Likewise, attempts to utilize the Ozawa method in the SiO 2 and CaCO 3 NA systems showed unacceptable nonlinear behavior in both the neat HDPE and composites during both primary and secondary crystallization phases . In all cases, this discrepancy was attributed to factors neglected in the Ozawa theory including secondary crystallization and dependence of lamellar thickness on the T c .…”
Section: Nonisothermal Crystallization Kineticsmentioning
confidence: 67%
“…The constant is an empirical pre‐exponential factor. Plots of dX t / dt versus 1/ T yield a straight line with slope equal to –Δ E / R .…”
Section: Activation Energymentioning
confidence: 96%
See 2 more Smart Citations
“…Mo's method [11,12,[28][29][30] is another efficient approach derived from the combination of both Avrami equation and Ozawa model [10], which have been successfully utilized in various cases [29,31,32]. Dividing the Avrami equation by the Ozawa's equation, functions are given in Equations (7) and (8): …”
Section: B-mo's Methodsmentioning
confidence: 99%